2022
DOI: 10.1371/journal.ppat.1010334
|View full text |Cite
|
Sign up to set email alerts
|

Widespread emergence of OmpK36 loop 3 insertions among multidrug-resistant clones of Klebsiella pneumoniae

Abstract: Mutations in outer membrane porins act in synergy with carbapenemase enzymes to increase carbapenem resistance in the important nosocomial pathogen, Klebsiella pneumoniae (KP). A key example is a di-amino acid insertion, Glycine-Aspartate (GD), in the extracellular loop 3 (L3) region of OmpK36 which constricts the pore and restricts entry of carbapenems into the bacterial cell. Here we combined genomic and experimental approaches to characterise the diversity, spread and impact of different L3 insertion types … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 56 publications
3
24
0
Order By: Relevance
“…In our study, we confirmed that, in KPC producing- K. pneumoniae strains, mutations in the porine gene omp K36 were present and, as previously observed by other Authors ( Venditti et al., 2021 ) presumably correlate with high-level resistance to carbapenems ( Wong et al., 2019 ; David et al., 2022 ). In addition to the indel found in the omp K36 gene, our isolates harbored frameshift mutations in omp K35 and omp K37, leading to nonfunctional proteins, associated, also in this case, with lower carbapenemase MICs, as already described by other Authors ( Gaibani et al., 2020 ; Venditti et al., 2021 ).…”
Section: Discussionsupporting
confidence: 91%
“…In our study, we confirmed that, in KPC producing- K. pneumoniae strains, mutations in the porine gene omp K36 were present and, as previously observed by other Authors ( Venditti et al., 2021 ) presumably correlate with high-level resistance to carbapenems ( Wong et al., 2019 ; David et al., 2022 ). In addition to the indel found in the omp K36 gene, our isolates harbored frameshift mutations in omp K35 and omp K37, leading to nonfunctional proteins, associated, also in this case, with lower carbapenemase MICs, as already described by other Authors ( Gaibani et al., 2020 ; Venditti et al., 2021 ).…”
Section: Discussionsupporting
confidence: 91%
“…We have recently shown that a GD insertion in L3 of OmpK36 in the recipient affected MPS formation with donors harbouring TraNβ 15 . More recently, while screening for other L3 insertions in a global genome collection of 16,086 K. pneumoniae isolates, we found Threonine-Aspartate (TD) and Aspartate (D) insertions in the important ST16 and ST231 lineages, respectively, which causes pore constriction of 41% and 8%, respectively 24 . Isogenic strains expressing these L3 insertions were recently generated from our wild type (WT) K. pneumoniae strain, ICC8001, itself derived from ATCC 43816 to study the impact of pore constriction on bacterial fitness and resistance to carbapenems 24 .…”
Section: Resultsmentioning
confidence: 99%
“…B . The crystal structure of OmpK36 WT+D adopts an open (shown in red) and closed (shown in blue) conformation (PDB ID: 7Q3T) 24 . Both conformations restrict the pore diameter by 8% relative to the WT protein.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations